Expressing the Human Cholesteryl Ester Transfer Protein Minigene Improves Diet-Induced Fatty Liver and Insulin Resistance in Female Mice - Zhu, Lin; An, Julia; Chinnarasu, Sivaprakasam; Luu, Thao; Pettway, Yasminye D.; Fahey, Kelly; Litts, Bridget; Kim, Hye-Young H.; Flynn, Charles R.; Linton, MacRae F.; Stafford, John M. (Frontiers in Physiology, 2022)
Mounting evidence has shown that CETP has important physiological roles in adapting to chronic nutrient excess, specifically, to protect against diet-induced insulin resistance. However, the underlying mechanisms for the protective roles of CETP in metabolism are not yet clear. Mice naturally lack CETP expression. We used transgenic mice with a human CETP minigene (huCETP) controlled by its natural flanking region to further understand CETP-related physiology in response to obesity. Female huCETP mice and their wild-type littermates were fed a high-fat diet for 6 months. Blood lipid profile and liver lipid metabolism were studied. Insulin sensitivity was analyzed with euglycemic-hyperinsulinemic clamp studies combined with 3H-glucose tracer techniques. While high-fat diet feeding induced obesity for huCETP mice and their wild-type littermates lacking CETP expression, insulin sensitivity was higher for female huCETP mice than for their wild-type littermates. There was no difference in insulin sensitivity for male huCETP mice vs littermates. The increased insulin sensitivity in females was largely caused by the better insulin-mediated suppression of hepatic glucose production. In huCETP females, CETP in the circulation decreased HDL-cholesterol content and increased liver cholesterol uptake and liver cholesterol and oxysterol contents, which was associated with the upregulation of LXR target genes in long-chain polyunsaturated fatty acid biosynthesis and PPAR target genes in fatty acid -oxidation in the liver. The upregulated fatty acid -oxidation may account for the improved fatty liver and liver insulin action in female huCETP mice. This study provides further evidence that CETP has beneficial physiological roles in the metabolic adaptation to nutrient excess by promoting liver fatty acid oxidation and hepatic insulin sensitivity, particularly for females.